Simbol dan makna dalam Pantun Melayu Bingkisan Permata / Eizah Mat Hussain - Eizah , Mat Hussain (2016)
This study analyzed pantun, in Pantun Melayu Bingkisan Permata (2001), a literary works by Harun Mat Piah published by Yayasan Karyawan. Pantun is analyzed by using the methodology of Malay Literature Poetics by Muhammad Salleh which focusing on one of the principles of the concept Yang Indah-Indah: the Beautiful, in Aesthetics of Malay Literature. The analysis will used three of the sub-principles in Yang Indah-Indah: the Beautiful, from Aesthetics of Malay Literature which are world wide condensed and compacted, the role of kiasan and suggestion and a world of dualities which used to exemplify the elegancy and beauty expressed in pantun. The beautiness of the poetry in this study focuses on symbols and meanings expressed in the pantun. The problem of study is designed from the obscurities in understanding the symbols and meanings which could lead to misinterpretation by readers and listeners to the pantun. The symbol has symbolic meanings in expressing the elusive connotation of the symbol, but symbol also has no connotation to be conveyed on the other times. It can be seen and demonstrated that symbols which are predominant in the poetry of flora and fauna symbols contains meaning in layers that need to be interpreted carefully and clearly. Meanwhile, the objectives of this study is to identify the symbols and meanings by using the principle of Yang Indah-Indah: the Beautiful, from Aesthetics of Malay Literature, to analyze the symbols and meanings of flora and fauna in the pantun and to assess the symbols and meanings of flora and fauna in Pantun Melayu Bingkisan Permata. The study finding shows that these three objectives have been achieved. As conclusion, to elaborate the beautiness in pantun by using symbols and meaning, we should consider the methodology of Poetics of Malay Literature in order the see the esthetics of pantun from the view of the Malays.